Evaluation of Pseudomonas chlororaphis subsp. aurantiaca SR1 for growth promotion of soybean and for control of Macrophomina phaseolina - Rovera, Marisa (2014)
Pseudomonas chlororaphis subsp. aurantiaca SR1 was evaluated for control of Macrophomina phaseolina in vitro and in soybean plants, for growth promotion of soybean plants and for production of antifungal compounds. Strain SR1 caused a significant inhibition of M. phaseolina in vitro and reduced damping-off in the in vivo assays. In addition, strain SR1 significantly increased shoot and root length and shoot and root dry weight of soybean plants in M. phaseolina infested soil, as compared to control plants in infested soil. Fragments for the phenazine-1-carboxylic acid, pyrrolnitrin and hydrogen cyanide encoding genes were amplified from the DNA of strain SR1 after polymerase chain reaction (PCR) assays with specific primers. Thus, this study establishes that P. chlororaphis subsp. aurantiaca SR1 provides control of M. phaseolina in vivo and suggests that strain SR1 might be applied as an effective biocontrol agent to protect soybean plants from this phytopathogen.